1992
DOI: 10.1111/j.2042-7158.1992.tb05514.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenobarbitone Population Pharmacokinetics from Routine Clinical Data: Role of Patient Characteristics for Estimating Dosing Regimens

Abstract: Routine clinical pharmacokinetic data collected from patients receiving phenobarbitone have been analysed to evaluate the role of patient characteristics for estimating dosing regimens. The data were analysed using NONMEM, a computer program designed for population pharmacokinetic analysis that allows pooling of data. The pharmacokinetic model of phenobarbitone was described using a one-compartment steady-state model. The effect of a variety of developmental and demographic factors on clearance was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
18
1
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 15 publications
8
18
1
1
Order By: Relevance
“…These results suggest that Ccr is a useful indicator of renal function in the prediction of Css, as indicated in previous reports [10,11].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results suggest that Ccr is a useful indicator of renal function in the prediction of Css, as indicated in previous reports [10,11].…”
Section: Discussionsupporting
confidence: 89%
“…of a Japanese population, similar to the present study, and reported that the precision of their method was superior to other methods [11]. Because they reported the precision of their predicted Css and dosage of lithium, there may be a discrepancy in the precision of predicted Li-CL between their and the present studies.…”
Section: Citationsupporting
confidence: 72%
See 1 more Smart Citation
“…The values for clearance determined in the present study are comparable with those previously determined using both traditional [5,7,8] and NONMEM [2] methods. The final model describing clearance included total body weight, the parameter which was also the most important fixed effect parameter, ahead of age, in the large Japanese study [2].…”
Section: Discussionsupporting
confidence: 78%
“…Studies have shown that the pharmacokinetics of PB in children and young adults is age-dependent, and may have an absolute bioavailability of 48.9% among the pediatric population (Yukawa, Higuchi, Aoyama, 1992;Marsot et al, 2013). In addition, comparing oral administration with the intramuscular route, there is a difference of about 60% in terms of bioavailability in newborns (Yukawa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%